Preliminary Study on the Use of Chemical Pesticides in Beir Bullerjam's Farms, Suluq, Libya - M. Abdullah , Marei; A. A. Alhursh , Adrees; M. O. Alajeeli , Shuayb (Scientific Journal of University of Benghazi, 2024)
Pesticides in Libya have increased recently in the agriculture sector to control pests, consequently improving field and horticultural crop productivity. The present study was undertaken to assess the current pesticide utilization among farmers in different farms across Beir Bullerjam's area. Data were collected from farmers using a structured questionnaire containing the following (socio-demographic details, awareness and knowledge, and farmer practices). Our results show that all farmers were male (100%), their farming experience was 13 years, and their average age was 46 years old. Not surprisingly, farmers did not know the modes or the compositions of pesticides being used and relied mainly on pesticide commercial retailers' knowledge. The most commonly used pesticides were: insecticides, herbicides, acaricides, and fungicides (47%), (34%), (18%), and (2%) respectively. Moreover, their trade names were: Oscar wp® 50, Roundup, Gramoxyone (herbicides), AQ Dorsban*4, Permethrin, Cyberkill 25, Mospy-one 20% sp, Fl-oil, Voliam Targo (insecticides), Vertimec (acaricide), and Strike (fungicide), and they were regularly utilized by farmers in this survey. We found that farmers reuse the same pesticides over years which may result in pesticide resistance of the targeted pest. Additionally, heavy use of insecticides by farmers could harm bee populations negatively in the region or decrease the natural enemies of pests. Farmer's awareness and attitudes towards pesticide use must be improved through agriculture extension agents or workshops for better food, healthy people, and ecosystems.